Poetisation of nature and thinking: a comparative analysis of the projects of M. Heidegger and R. W. Emerson - Alexandrov, Emile (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
Scholarship of Martin M. Heidegger’s relation to R. W. Emerson is seldom conducted, notwithstanding limited engagement on the part of S. Cavell. Considering the influence R. W. Emerson had on F. Nietzsche, and the significant influence the latter had on M. Heidegger, any necessary relation needs to be studied. The author of this paper confirms this relatability in the role that nature plays in the writings of both M. Heidegger and R. W. Emerson. Both thinkers show that in the poetising of nature, the poet is not making assertions as such, rather imparting upon receiving from nature as that which «educates». The author reveals this feature to be central to the poet figure of both M. Heidegger and R. W. Emerson, and both agree that it is exhibited by few remarkable figures throughout history. However, the limit of their congruency, as the author argues, is in M. Heidegger and R. W. Emerson’s disagreement regarding the relation of poetry to thought.